SYNBIO® Probiotic and Antioxidant Dietary Supplementation: Clinical Trial Evaluation of Potential Effects on Airline Flight Crew Members’ Well-Being - Maria Magdalena Coman; Maria Vittoria Micioni Di Bonaventura; Carlo Cifani; Stefania Silvi; Maria Cristina Verdenelli (Microorganisms, 2023)
The irregular lifestyle of airline crew members, wide/adverse job-related exposures, and the impact of temporary hypoxia on gut microbiota well-being have increased concern about the daily recommended dose of certain nutrients among flight crew. The aim of this study was to determine if daily consumption of a SYNBIO® probiotics–elderberry extract supplement (ACTIVE) may contribute to the well-being of flight attendants. Forty healthy crew members enrolled in a double-blind, randomized, placebo-controlled study consumed one ACTIVE capsule/day or placebo for 30 days. Bowel well-being, health-related quality of life, and gastrointestinal tolerance were assessed by validated questionnaires. Saliva and fecal samples were analyzed to determine secretory immunoglobulin-A (sIgA) levels and to characterize gut microbiota composition, respectively. ACTIVE subjects presented a physiological improvement and a statistically significant higher Psychological General Well-Being Index (PGWBI) global score compared to PLACEBO subjects. The ACTIVE subjects showed significantly increased levels of lactobacilli and bifidobacteria compared to the PLACEBO group, while a significant increase in lactobacilli and a significant reduction in Enterobacteriaceae were registered when compared with the beginning of supplementation, confirming the persistence of probiotics in the gastrointestinal tract and the direct antagonism and competitive exclusion effects. Additionally, sIgA levels were significantly higher in the ACTIVE group compared to the baseline and to the PLACEBO group at the end of supplementation. The ACTIVE supplementation might be beneficial to airline crew members, improving their physiological state, their immune defenses, and the strength and efficiency of their gastrointestinal tract when responding to stressful conditions.